(untitled) (Medical Forum Monthly, 2026)
Objective: The aim of the narrative review is to compare the incidence of the malignant transformation of oral lichen planus (OLP) and oral lichenoid lesions (OLL) in patients. Place and Duration of Study: The literature review was undertaken at the Department of Oral and Maxillofacial Diagnostic Sciences, College of Dentistry, Qassim University, Saudi Arabia from January 2025 to May 2025. Methods: The review of literature was undertaken with the help of electronic data bases, including Web of Science, PubMed, Google Scholar, Scopus, Medline, Embase, NCBI, Elsevier. The following keywords were used to search for the present study: oral lichen planus, oral lichenoid lesions, malignant transformation, and diagnostic challenges: 2014, May 2024. Results: The reported rates of malignant transformation of OLP and OLL ranged from 0 to 5.4. The incidence of malignant transformation in OLP is uncertain due to overlap with OLL and with early-stage oral squamous cell carcinoma (OSCC) and lichenoid lesions. Conclusion: Malignant transformation risk in OLP and OLL is variable with a low average risk. However, a combination of clinical and histological features complicates risks assessment and there is a need to put more emphasis on follow-up and consistent diagnosis.